The effect of the online eye movement desensitization and reprocessing early intervention protocol (EMDR R-TEP) for the risk groups with post-traumatic stress symptoms during the COVID-19 pandemic - Yurtsever, Asena; Bakalim, Orkide; Karaman, Şenel; Kaya, Sefa; Konuk, Emre (Frontiers in Psychology, 2022)
The aim of the research is to investigate the effect of eye movement desensitization and reprocessing (EMDR) therapy on post-traumatic stress disorder (PTSD) levels of individuals who can be defined as high-risk groups during the pandemic. Therefore, the online EMDR R-TEP Protocol was applied to a total of 154 individuals working with coronavirus patients, frontline professionals (Doctors, Nurses, Paramedics, Polices, Red Crescent), relatives of coronavirus patients, coronavirus patients, and relatives of someone who died from coronavirus and the PTSD symptom level before, after, and 1 month after therapy was measured and examined. A personal information form and impact of events scale were used to collect data. Analyses showed that EMDR therapy was effective in reducing the PTSD level in all groups. The PTSD levels of frontline professionals continued to decrease until the follow-up test but remained the same in the other groups.